Vanadate sensitive ATPase and phosphatase activity in guard cell protoplasts of Commelina - Fricker, M; Willmer, C (1987)
Flicker, M. D. and Willmer, C. M. 1986. Vanadate sensitive ATPase and phosphatase activity in guard cell protoplasts of Commelina.-J. exp. Bot. 38: 642-648.Phosphatase activity was measured in extracts of guard cell protoplasts of Commelina communis L. using the artificial substrate p-nitrophenylphosphate. A pH optimum of 5.8 to 6.3 was determined. Ammonium molybdate (Ol mol m -3) and sodium vanadate (1-0 mol m -3) gave almost complete inhibition of phosphatase activity at pH 60. ATPase assays were, therefore, conducted in the presence of 0-2 mol m -3 molybdate and vanadate was used as a specific inhibitor of plasmamembrane ATPase activity. Vanadate sensitive ATPase activity showed a pH optimum of 6.6 and activity was stimulated by KC1. These properties are characteristic of plasmamembrane proton pumping ATPases in other systems and suggest that proton extrusion in guard cells could be mediated by a similar enzyme. The maximum ATPase activity is sufficient to account for all the proton flux observed during the stomatal opening response. © 1987 Oxford University Press.